2000
DOI: 10.1002/etc.5620190606
|View full text |Cite
|
Sign up to set email alerts
|

Dietary accumulation and quantitative structure‐activity relationships for depuration and biotransformation of short (C10), medium (C14), and long (C18) carbon‐chain polychlorinated alkanes by juvenile rainbow trout (Oncorhynchus mykiss)

Abstract: Abstract-Juvenile rainbow trout (Oncorhynchus mykiss) were exposed to three [ 14 C]-polychlorinated alkanes (PCAs) (C 10 H 15.3 Cl 6.7 , C 14 H 23.3 Cl 6.7 , and C 18 H 31.4 Cl 6.6 ) at nominal concentrations of 1.5 and 15 g/g for 40 d, followed by 160 d of clean food, to measure bioaccumulation parameters and biotransformation. These PCAs are identical in carbon-chain length and chlorine content to industrial chlorinated paraffin products, although their method of synthesis differs from that of chlorinated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 35 publications
4
72
1
Order By: Relevance
“…A similar pattern of decreasing BMFs with the increasing carbon chain length of SCCP congeners was observed in a food web from Lake Michigan (Houde et al, 2008). However, in previous laboratory exposure experiments, the BMFs tended to increase with increasing lengths of the carbon chain (Fisk et al, 1998;Fisk et al, 2000). Notably, the biomagnification of shorter chain congeners of SCCPs was higher than that of the longer chain ones in the field study, which might be attributed to the larger molecular sizes of the longer carbon chain congeners, as Mackintosh et al (2004) found that the concentrations of high molecular-weight phthalate esters declined significantly at higher trophic levels in a marine food web from western Canada.…”
Section: Bioaccumulation and Biomagnification Of Sccpssupporting
confidence: 70%
“…A similar pattern of decreasing BMFs with the increasing carbon chain length of SCCP congeners was observed in a food web from Lake Michigan (Houde et al, 2008). However, in previous laboratory exposure experiments, the BMFs tended to increase with increasing lengths of the carbon chain (Fisk et al, 1998;Fisk et al, 2000). Notably, the biomagnification of shorter chain congeners of SCCPs was higher than that of the longer chain ones in the field study, which might be attributed to the larger molecular sizes of the longer carbon chain congeners, as Mackintosh et al (2004) found that the concentrations of high molecular-weight phthalate esters declined significantly at higher trophic levels in a marine food web from western Canada.…”
Section: Bioaccumulation and Biomagnification Of Sccpssupporting
confidence: 70%
“…26,2007 J.W. Low (0.0-0.0084/d) rates of metabolism were exhibited by juvenile trout exposed to a series of polychlorinated alkanes [49]. One potential use of these models is to perform in vitro-in vivo metabolism comparisons with fish.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism of chlorinated paraffins in organisms has been noted in several studies. For example, Fisk et al (2000) and Vaughan and Hurd (2010) observed significant biotransformation of chlorinated alkanes in rainbow trout (Oncorhynchus mykiss). Houde et al (2008) also found that lake trout metabolize SCCPs.…”
Section: Species Difference In Sccp Levels and Potential Impact Factorsmentioning
confidence: 99%